Surface-modified titanium and titanium-based alloys for improved osteogenesis: A critical review - Jingling Li; Yaxin Zheng; Zihe Yu; Ranjith Kumar Kankala; Qianying Lin; Jingbo Shi; Chao Chen; Kai Luo; Aizheng Chen; Quan Zhong (Heliyon, 2024)
As implantable materials, titanium, and its alloys have garnered enormous interest from researchers for dental and orthopedic procedures. Despite their success in wide clinical applications, titanium, and its alloys fail to stimulate osteogenesis, resulting in poor bonding strength with surrounding bone tissue. Optimizing the surface topology and altered compositions of titanium and titanium-based alloys substantially promotes peri-implant bone regeneration. This review summarizes the utilization and importance of various osteogenesis components loaded onto titanium and its alloys. Further, different surface-modification methods and the release efficacy of loaded substances are emphasized. Finally, we summarize the article with prospects. We believe that further investigation studies must focus on identifying novel loading components, exploring various innovative, optimized surface-modification methods, and developing a sustained-release system on implant surfaces to improve peri-implant bone formation.